The Mechanism Research for the Surface Plasmon-Catalysed Reaction of the Mercapto Group Substituted Benzoic Acid (Journal of Atomic and Molecular Sciences, 2017)
In this study, we experimentally investigated the substituent effect on benzoic acid where the mercapto group was located in different positions, namely as 2-mercaptobenzoic acid (2-MBA), 3-mercaptobenzoic acid (3-MBA) and 4-mercaptobenzoic acid (4-MBA). The substituent effect was found to have an influence on the surface plasmon-catalysed reaction on the surface of the Ag4 atoms in the reaction of MBA with silver sol. In addition to the direct evidence from the surface-enhanced Raman scattering (SERS), the chemical enhancement mechanism for the generation of the MBA-Ag complex is presented. In contrast with the normal Raman scattering (NRS) spectra, new signals appeared in the SERS spectra of 2-MBA, 3-MBA and 4-MBA under the theoretical and experimental conditions. On investigation of the SERS spectra, the characteristic peaks of the C ≡ C bond have been demonstrated. The structural, atomic and chemical bond properties of the three types of MBAs indicate that the S atom of the mercapto group in the MBA molecules is the position site that attaches to the silver substrate through the bond of S…Ag, and under laser irradiation, “hot electrons ”  are generated between the surface of MBA and Ag4 atoms. With the effect of “hot electrons ” , the -COOH bond of the MBA molecules is broken, and then the two single carboxylate MBA molecules become dimerized thiophenol acetylene (TPA). To briefly consider the substituent effect, the SERS spectra of these three types of MBAs were specifically studied for the enhancement of the Raman signal intensity with a variational tendency evident. Therefore, the conclusion was reached that the substituent effect plays a vital role in the surface plasmon-catalysed reaction, where the changing of the surface-enhanced Raman intensity was demonstrated.